A Case Report of Dilacerated Crown of a Permanent Mandibular Central Incisor - Behnam Bolhari; Salma Pirmoazen; Ensieh Taftian; Somayeh Dehghan (Tehran University of Medical Sciences, 2017)
Trauma to primary teeth can lead to devastating sequels in development of permanent successors. The disturbance may range from enamel hypoplasia and/or hypo-calcification to arrest of dental bud development. Crown dilaceration of permanent teeth is one of the consequences of trauma to deciduous teeth mainly due to intrusion or avulsion. This report presents a mandibular central incisor with dilacerated crown and yellowish discoloration with symptomatic apical abscess. History revealed avulsion of primary mandibular central incisors. The purpose of this report is to present: 1. Reasons of dilacerated crown, yellowish discoloration and necrotic pulp in this case, 2. Treatment options in different types of crown dilacerations and also in this case. The tooth was successfully managed by nonsurgical root canal therapy and restoration with composite resin to restore esthetics. We emphasize that trauma to deciduous teeth should not be understated, and regular follow up is essential.